Co-operative Societies - Connor, Frederic W. (Dublin Statistical Society, 1862)
Co-operative societies, cautiously conducted, might act perhaps as indices of the normal rate of wages and the normal condition of labour throughout the various trades ; if they are compelled to lower wages or to curtail a privilege, the workman knows that it must be, and the whole trade accordingly submits to the reduction or curtailment. While pointing out the difficulties that beset the path of co-operative manufactories, we extend to them the truest help. We heartily wish them success, hoping that wisdom will be gained, if not wealth, from the industry, self-control, and mutual forbearance needed to conduct them; at the same time trusting that they may reap the full reward of that energy which springs from freedom, and participate in that progress which waits on self-reliance ; trusting still more strongly that such associated workshops may become the sanctuaries of honest work, upright fellowship, and manly independence, which by infusing individual sympathy into united action may create around them an atmosphere of Christian love.
Read Monday evening, 20th January, 1862
Keywords: Cooperative Societies; 314.15